A meta-analysis and systematic review of Memory Specificity Training (MeST) in the treatment of emotional disorders. (May 2019) - Barry, Tom J.; Sze, Wing Yan; Raes, Filip
Abstract: The tendency to recall events from one's past in a non-specific and overgeneral way has been found to predict the onset and severity of a range of emotional disorders. Memory Specificity Training (MeST) was devised a decade ago in order to target and modify this tendency so as to reduce the symptoms of emotional disorder or to reduce the risk that such disorders might emerge over time. We present a meta-analytical review of research into the effects of MeST on autobiographical memory specificity in the context of emotional disorders ( k  = 13). MeST was associated with substantial improvement in memory specificity ( d  = −1.21) and depressive symptoms ( d  = 0.47) and MeST groups outperformed control groups at post-intervention in terms of specificity ( d  = 1.08) and depressive symptoms ( d  = −0.29). However, these effects were transitory and the benefit of MeST over control groups was mostly lost by follow-up assessment. There was mixed evidence in terms of MeST's effects on other processes associated with reduced specificity but MeST showed evidence of improving problem solving abilities and hopelessness. MeST holds promise as a novel intervention targeting reduced specificity but future studies are warranted with control groups that enable the investigation of MeST's mechanism of action and in studies with larger and more varied samples. Highlights: People with a range of emotional disorders often recall their memories with little specificity. Memory Specificity Training (MeST) leads to improvements in specificity relative to controls. MeST is also associated with improved depression symptoms and other associated processes relative to controls. However, these effects are confined to post-intervention assessment and do not persist to follow-up.